BODY MEASUREMENTS AS BASIS OF ESTIMATION OF LIVE WEIGHT IN GROWING SAHIWAL CATTLE - VANDANA BHAGAT , VIKAS KHUNE , MANJU ROY; SAMBHUTI SHANKAR SAHU AND KRANTI SHARMA (The Bioscan, 2018)
The present research was undertaken with an aim to derive prediction equation based on body measurements in different age groups of growing Sahiwal calves. Sahiwal cattle’s which are divided into five age groups (0-6, 6-12, 12-18, 18-24 and 24-30 months) and mean values of various body parameter are as follow Body length (BL), Heart Girth (HG), Height at withers (HT), Head to shoulder length (HAW) and Chest depth (CD) (54.22±2.47, 123.53±5.83, 141.44±3.80, 156.89±3.52 and 199.48±7.39kg), (69.91±1.01, 94.70±1.22, 100.51±1.36, 102.32±0.85 and 107.33±1.87cm), (85.14±1.61, 109.34±2.19, 122.20±1.74, 125.41±0.94 and 132.20±1.38cm), (77.44±1.02, 97.75±1.21, 101.88±1.31, 103.26±0.62 and 108.18±1.10cm), (34.74±0.46, 43.86±0.85, 47.88±0.74, 48.13±0.70 and 52.03±0.75)(31.90±0.68,41.11±0.96, 45.96±0.96, 46.21±1.12 and 50.06±0.6cm), respectively. Best fitted BW Prediction model developed on the basis of multiple linear regression of two independent variables (HG and BL), three independent variables (BL, HG and HAW) and four independent variables (BL, HG, WAH and HS) were significant (P<0.05) with R2 values of 0.86, 0.86, and 0.87 respectively